Disasters in Germany and France: an analysis of the emergency events database from a pediatric perspective - Ries, Markus; Zielonka, Matthias; Ries, Noah; Breil, Thomas; Garbade, Sven; Mechler, Konstantin (Disaster medicine and public health preparedness, 2019)
Objective:The objective of this study was to conduct comprehensive analyses of disaster patterns for Germany and France from a pediatric perspective.Methods:An analysis of the Emergency Events Database (EM-DAT), epidemiological database with standard methods of descriptive and comparative statistics respecting the strengthening the reporting of observational studies in epidemiology (STROBE) criteria, was performed.Results:Between 2006 and 2016, there were 41 and 42 disasters in Germany and France claiming 259 and 4973 lives, respectively. Ages of afflicted individuals were not specified in EM-DAT. In Germany, most events were storms (37%), extreme temperatures (17%), floods (17%), and transport accidents (17%). In France, most events were storms (45%), extreme temperatures (17%), floods (19%), and transport accidents (14%). In Germany, most lives (96) were lost in transport accidents. In France, most casualties were due to the heat waves of 2006 and 2015 (1388 and 3275). Reported event types in Germany and France were similar, but heat waves struck France more significantly than Germany.Conclusions:Pediatric data are not explicitly captured in EM-DAT, but reported disaster patterns suggest that exposures to heat and cold, storms, trauma, chemicals, water, and infectious agents are possible mechanisms of injury. Age-stratified disaster data are needed to enable a timely, transparent, coordinated, and sustained data-driven approach to pediatric disaster resilience.
Gesehen am 20.01.2020